Perspectives for digital social innovation to reshape the European welfare systems - Davide, F. (Fabrizio); Gaggioli, Andrea; Misuraca, Gianluca (Emerging communication ;, 2021)
Social welfare is riddled with ingrained problems that have already defeated all standard approaches, and reform calls for counterintuitive action. Digital Social Innovation (DSI) is primarily about promoting grassroots initiatives to address localized societal problems, and is not normally talked about in relation to welfare reform, but perhaps social innovation initiatives, with their localized and case-based approach, could help to solve the enormous structural problems faced by our welfare democracies today.this book addresses the potential and implications of DSI for the reform of the European welfare state. The 14 papers collected here focus on key issues, such as the nature of social innovation and its effects; scaling up to address structural problems and make systemic change; new social risks and challenges; the role of digital thinking and emerging technologies; public governance approaches; tolerance of institutions; integrating innovation in the welfare system; and the empowerment of marginalized citizens. These topics are examined from an integrated and multi-disciplinary perspective, taking into consideration not only current EU debate on policy trends for social protection, but also the nature of digital transformation and its effects on social change. The book also highlights barriers to adoption, as well as the potential limitations and failures of this emerging approach.